FTIR analysis of gases evolved from cotton and flame retarded cotton fabrics pyrolysed in air - (:unkn) unknown (ELSEVIER SCI LTD, 1996)
The gaseous products produced by pyrolysing various samples of cotton and flame retarded cotton fabrics in air at different temperatures (300-1200 degrees C) were identified and quantified via FTIR. CO and CO2 evolutions were investigated in detail. The flame retardant samples showed enhanced CO and CO2 concentrations at lower pyrolysis temperatures (300-450 degrees C). These evolutions showed similar temperature dependence behaviour for all samples tested. At higher temperatures (450-800 degrees C), a second pyrolysis stage is identified where product evolution increased in concentration towards respective maximum values within this range. At higher temperatures still (800-1200 degrees C) pyrolysis product oxidation occurred which thus reduced the concentrations of all oxidisable products. The relative evolutions of both CO and CO2 are commensurate with the known vapour phase and condensed phase activities of bromine- and phosphorus-nitrogen-containing flame retardants, respectively. (C) 1996 Elsevier Science Limited.
Keywords: SINGLE LAYER FABRICS; CO EVOLUTION; INVESTIGATE; CELLULOSE; BEHAVIOR; SMOKE